Antibody Responses to mRNA COVID-19 Vaccine Among Healthcare Workers in Outpatient Clinics in Japan - Teruhime Otoguro; Keita Wagatsuma; Toshiharu Hino; The Society of Ambulatory and General Pediatrics of Japan; Yusuke Ichikawa; Tri Bayu Purnama; Yuyang Sun; Jiaming Li; Irina Chon; Hisami Watanabe; Reiko Saito (Vaccines)
Background: This study aimed to assess the antibody response to SARS-CoV-2 vaccines among healthcare workers (HCWs) from multiple outpatient clinics in Japan, examining the effects of baseline characteristics (e.g., sex, age, underlying condition, smoking history, occupation) and prior infections. Methods: A total of 101 HCWs provided serum at four time points between October 2020 and July 2023. HCWs received two to six doses of mRNA vaccine (BNT162b2 or mRNA-1273). Anti-nucleocapsid (N) and anti-spike (S) IgG antibodies against the ancestral Wuhan strain were measured using the Abbott Architect™ SARS-CoV-2 IgG assay. Univariate and regression analysis evaluated factors such as past infections, age, sex, smoking, underlying condition, and occupation. Results: After four to six doses, the median anti-S IgG titer in uninfected HCWs was 1807.30 BAU/mL, compared to 1899.89 BAU/mL in HCWs with prior infections. The median anti-N IgG titer was 0.10 index S/C in uninfected HCWs and 0.39 index S/C in infected HCWs. HCWs with prior infection had anti-S IgG titers 1.1 to 5.8 times higher than those without. Univariate and multivariate analyses indicated infection and vaccination significantly increased anti-S and anti-N IgG titers. Age, sex, smoking history and occupation did not influence antibody titers while underlying conditions were associated with lower anti-N IgG titers. Conclusions: Infection and vaccination were strongly associated with an increase in anti-S and anti-N IgG titers; however, the impact of hybrid immunity appeared to be limited and varied depending on the timing of the sampling. These findings provide valuable insights for developing personalized vaccination strategies and future vaccine development.